COMMUNITY SATISFACTION LEVEL WITH THE QUALITY OF PUBLIC SERVICES IN DIMITO VILLAGE - Sukrin Badu; Sudarsono; Ghoriqna Fibahril Wahdah (Journal of Economic, Business, and Administration (JEBA), 2024)
This study aims to measure the level of community satisfaction, evaluate the quality of public services, and analyze the influence of service quality on community satisfaction in Dimito Village, Wonosari District. This research employs a quantitative approach with a survey design. Data were collected from 80 respondents using research instruments (questionnaires) and analyzed using simple linear regression via SPSS. The results indicate that public service delivery in Dimito Village generally aligns with the Ministry of State Apparatus Empowerment and Bureaucratic Reform Regulation No. 14 of 2017. Dimensions of simplicity and clarity received high appreciation, with 48.8% and 60% of respondents strongly agreeing with the performance in these areas, respectively. However, findings suggest a need for improvement regarding service duration (time efficiency) and security aspects. Statistical analysis confirms a positive and significant influence of service quality on community satisfaction, with a regression coefficient of 0.636. This implies that a 1% improvement in service quality significantly enhances community satisfaction by 63.6%. These results emphasize that optimizing administrative procedures and officer competence is vital for fostering public trust and welfare at the village level.